A geographic identification of sustainable development obstacles and countermeasures in drylands: A case study in Inner Mongolia, China. (December 2021) - Li, Tong; Jia, Yuantong; Fava, Francesco; Xu, Zhihong; Zhu, Jiapei; Yang, Yaqian; Tang, Li; Wang, Yanfen; Hao, Yanbin; Cui, Xiaoyong
Highlights: A sustainable livelihoods indicator across a geographical gradient of aridity was developed. Sustainable livelihoods vary greatly across dryland zones. Semi-arid zones have the most vulnerable livelihood rather than the arid zones. The lack of physical capital and social capital is an important obstacle to sustainable livelihoods development in drylands. Call for integrated land management and planning approach in drylands. Abstract: Drylands cover about 41% of the Earth's land surface and are inhabited by more than two billion people, who rely on the diversified ecosystem services provided by drylands for their livelihoods. Achieving sustainable livelihoods (SLs) is a key component of achieving the sustainable development goals set by the agenda in 2030. Although it has aroused extensive interest, research on SLs in drylands at a regional scale is still limited. This paper aims to address this research gap by evaluating SLs through a geographic gradient of aridity in Inner Mongolia. A sustainable livelihood index (SLI) was developed using a wide range of indicators in a sustainable livelihood framework (SLF). The weight of the indicators was determined by the entropy weight method, and the characteristics of the spatial distribution of the SLI were analyzed. The results showed that the SLI varies greatly across aridity zones. In terms of livelihood assets, the SLI in the dry sub-humid zone was 15% higher than in the arid zones, while, surprisingly, semi-arid zones were found to have the most vulnerable livelihoods (rather than the arid zones). The reason for this is that land management and planning approaches are necessary in drylands. In further detail, Moran's I index illustrated that the overall performance of the SLI of each league or city has a positive spatial correlation, while through local spatial correlation it was found that Hinggan and Chifeng are hot spot areas and Hohhot is a cold spot area. The lack of physical and social capital is an important obstacle for SLs. Based on the analysis of SLs in Inner Mongolia, the characteristics of the sustainable development of local residents were revealed. In this paper, we call for an integrated (i.e., focusing on natural and human capital) land management and planning approach for drylands to reflect the nature of the tightly coupled socio-ecological systems.